Aptamer-guided upconversion nanoplatform for targeted drug delivery and near-infrared light-triggered photodynamic therapy. (January 2020) - Lin, Hui-Chao; Li, Wen-Tian; Madanayake, Thushara W; Tao, Can; Niu, Qiang; Yan, Si-Qi; Gao, Bao-An; Ping, Zhao
Current photodynamic therapy faces two major challenges, which are the limited tissue penetration of excitation light and poor tumor selectivity of the photosensitizer. To address these issues, in the present work, a photosensitizer protoporphyrin IX was delivered by aptamer-coated upconversion nanoparticles. The aptamer, namely, AS1411, could fold to G-quadruplex structures with the bi-functions of loading protoporphyrin IX and targeting the cancerous cells. The protoporphyrin IX aptamer-coated upconversion nanoparticle nanospheres exhibited good biocompatibility, high nuclease resistance, and targeted cellular internalization. The receptor blocking experiment indicated that the cellular uptake of protoporphyrin IX aptamer-coated upconversion nanoparticle mainly attributed to the binding of AS1411 to the nucleolin overexpressed on the cancerous cell membrane. Moreover, high-efficient photodynamic therapy of the as-prepared protoporphyrin IX aptamer-coated upconversion nanoparticle nanospheres was achieved to cancerous cells under the irradiation of near-infrared light, which was induced by the upconversion property of the upconversion nanoparticle. These results indicate that the fabricated protoporphyrin IX aptamer-coated upconversion nanoparticle nanoplatform has higher efficiency, lower toxicity, and less side effects compared to the free photosensitizer protoporphyrin IX, and thus is a new promising photodynamic therapy agent especially for the deep-seated tumors.